A back film structure for simultaneously improving the efficiency of the back and front sides of a bifacial PERC cell, and a preparation method and application thereof
By using a back film structure composed of aluminum oxide, silicon nitride and silicon oxynitride films in P-type double-sided PERC solar cells, the problem of difficulty in improving the back efficiency in the prior art is solved, and the simultaneous efficiency improvement of the back and front surfaces is achieved.
Patent Information
- Application Number
- CN202011077745.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-10-10
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2040-10-10
Smart Images

Figure CN114420765B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of solar cells and relates to a back film structure for simultaneously improving the back and front efficiencies of a double-sided PERC, and a preparation method and application thereof. Background Art
[0002] In recent years, with the continuous advancement of solar cell production technology, the main research hotspots include HIT cells, WMT cells, N-type bifacial cells, P-type PERC cells, etc. Among them, P-type PERC cells have become the mainstream battery technology in the market due to their relatively mature technology and low difficulty in mass production. Compared with other new types of cells, the front efficiency of bifacial PERC solar cells is lower. The bifaciality of bifacial modules of mainstream manufacturers is 65-75%, and there is an urgent need to further improve the front and back efficiency of bifacial PERC solar cells. Therefore, improving the back film structure and optimizing the coating process, reducing the reflectivity of the back of the cell, increasing the absorption of light, improving the back conversion efficiency of P-type bifacial PERC cells, and improving the bifaciality of P-type bifacial PERC cells are the current focus of the industry.
[0003] CN110957378A discloses a back film structure for improving the bifaciality of a P-type bifacial cell, including a cell, an aluminum oxide film, a silicon nitride film, a silicon oxynitride film, and a silicon oxide film are sequentially deposited on the back of the cell, and the silicon nitride film includes an upper silicon nitride film, a middle silicon nitride film, and a lower silicon nitride film. The thickness of the upper, middle, and lower three silicon nitride films gradually increases, and the refractive index gradually decreases. The total film thickness of the silicon nitride film is 35 to 55 nanometers, and the total refractive index of the silicon nitride film is 2.12 to 2.20. By improving the back film structure and optimizing the coating process, the reflectivity of the back of the cell is effectively reduced, the absorption of light is increased, and the back conversion efficiency of the P-type bifacial SE PERC cell is improved. The bifaciality of the P-type bifacial SE PERC cell is increased from 72.9% to 74.14%. However, the invention needs to include three layers of silicon nitride films that meet the specific conditions as described above, which increases the complexity of the preparation process.
[0004] Therefore, in this field, it is expected to develop a simpler and more efficient back film structure that can improve the bifaciality of P-type bifacial cells. Summary of the invention
[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a back film structure and a preparation method and application thereof for simultaneously improving the efficiency of the back and front sides of a bifacial PERC. The back film structure of the present invention can simultaneously improve the efficiency of the back and front sides of a bifacial PERC.
[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0007] On the one hand, the present invention provides a back film structure for simultaneously improving the efficiency of the back and front sides of a double-sided PERC, wherein the back film structure comprises an aluminum oxide film located on the back side of a cell, a silicon nitride film disposed on the aluminum oxide film, and a silicon oxynitride film disposed on the silicon nitride film.
[0008] The back film structure described in the present invention is composed of the three-layer structure as described above, so that the efficiency of the back and front sides of the bifacial PERC can be improved at the same time. The back film structure has a better hydrogen passivation effect, which can improve the opening voltage and fill factor of the battery, thereby achieving an improvement in the front conversion efficiency, and can also improve the back conversion efficiency of the P-type bifacial PERC battery.
[0009] Preferably, the thickness of the aluminum oxide film is 5 to 15 nm (e.g., 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, 11 nm, 12 nm, 13 nm, 14 nm or 15 nm), and the refractive index is 1.55 to 1.63 (e.g., 1.55, 1.60, 1.63). In the present invention, if the thickness of the aluminum oxide film is less than 5 nm, the silicon surface recombination rate will increase, affecting its passivation effect; if the thickness of the aluminum oxide film is greater than 15 nm, the process time will be long, affecting the production capacity.
[0010] Preferably, the aluminum oxide film has a thickness of 8-10 nm and a refractive index of 1.56.
[0011] Preferably, the thickness of the silicon nitride film is 20 to 90 nm (e.g., 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, 55 nm, 60 nm, 70 nm, 80 nm or 90 nm), and the refractive index is 2.0 to 2.4 (e.g., 2.0, 2.1, 2.2, 2.3, 2.4). In the present invention, if the thickness of the silicon nitride film is less than 20 nm, the absorption of medium and long wave light is less, and the reflectivity will increase; if the thickness of the silicon nitride film is greater than 90 nm, the absorption of short wave light is less, and the reflectivity will also increase; if the refractive index of the silicon nitride film is less than 2.0, the passivation effect will deteriorate and the battery efficiency will decrease; if the refractive index of the silicon nitride film is greater than 2.4, the extinction coefficient will be very large, which will reduce the effective absorption of light by silicon, reduce the back current, and ultimately reduce the back efficiency.
[0012] Preferably, the silicon nitride film has a thickness of 60-80 nm and a refractive index of 2.1-2.4.
[0013] Preferably, the thickness of the silicon oxynitride film is 20 to 90 nm (e.g., 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, 55 nm, 60 nm, 70 nm, 80 nm or 90 nm), and the refractive index is 1.6 to 2.0 (e.g., 1.6, 1.7, 1.8, 1.9, 2.0). In the present invention, if the thickness of the silicon oxynitride film is less than 20 nm, the absorption of medium and long wave light is less, and the reflectivity will increase; if the thickness of the silicon oxynitride film is greater than 90 nm, the absorption of short wave light is less, and the reflectivity will also increase; if the refractive index of the silicon oxynitride film is less than 1.6, the effective H content will be low, affecting the passivation effect and reducing the front and back battery efficiency; if the refractive index of the silicon oxynitride film is greater than 2.0, it is difficult to complete the existing preparation process.
[0014] Preferably, the silicon oxynitride film has a thickness of 40-60 nm and a refractive index of 1.8.
[0015] Preferably, the total thickness of the aluminum oxide film, silicon nitride film and silicon oxynitride film is 80 to 160 nm, and the total refractive index is 2.10 to 2.35. In the present invention, if the total thickness of the entire film is less than 80 nm, the absorption of medium and long-wave light is less, and the overall reflectivity will increase. If the thickness of the silicon oxynitride film is greater than 160 nm, the absorption of short-wave light is less, and the overall reflectivity will also increase. In short, if the thickness of the entire film is too thin or too thick, it is not conducive to reducing the reflectivity and improving the efficiency of the back side of the battery.
[0016] The lowest point of the reflectivity curve of the back film structure of the present invention in the wavelength range of 300nm to 1200nm is located at 650 to 1000nm, for example, 650nm, 700nm, 750nm, 800nm, 850nm, 900nm, 950nm, and 1000nm.
[0017] Preferably, the lowest point of the reflectivity curve of the back film structure in the wavelength range of 300nm to 1200nm is located at 850 to 950nm.
[0018] The back film structure of the present invention has an average reflectivity of 7.5% to 11% in the wavelength range of 300nm to 1200nm, for example, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5% or 11%.
[0019] On the other hand, the present invention provides a method for preparing a back film structure for simultaneously improving the efficiency of the back and front sides of a bifacial PERC as described above, the preparation method comprising the following steps:
[0020] A. Place the cell with the back side facing up into the graphite plate, then place the graphite plate into the ALD plate chamber to coat a layer of aluminum oxide film on the back side of the cell;
[0021] B. Place the battery cell obtained in step A with the back side facing upward into a graphite boat, then place the graphite boat into a tubular PECVD, introduce ammonia and silane gases, and coat the aluminum oxide film to prepare a silicon nitride film;
[0022] C. introducing laughing gas, ammonia and silane to coat the silicon nitride film to prepare a silicon oxynitride film, thereby obtaining the back film structure.
[0023] Preferably, the silane in step B is SiH4.
[0024] Preferably, the flow ratio of ammonia and silane introduced in step B is 8:1 to 3:1, for example, 8:1, 7:1, 7.5:1, 6:1, 6.5:1, 5:1, 4:1 or 3:1.
[0025] Preferably, the coating power in step B is 8 kilowatts and the duty cycle is 1:15.
[0026] Preferably, the coating time in step B is 300-600 s, for example, 300 s, 350 s, 380 s, 400 s, 450 s, 500 s, 550 s or 600 s.
[0027] Preferably, the coating temperature in step B is 450-500°C, such as 450°C, 470°C, 490°C or 500°C.
[0028] Preferably, the flow ratio of laughing gas, ammonia and silane introduced in step C is 14:2:1 to 5:0.5:1, for example, 14:2:1, 14:1.8:1, 14:1.2:1, 14:1:1, 14:0.8:1, 12:0.8:1, 13:0.5:1, 8:0.8:1, 7:1.5:1, 6:0.5:1, 5:2:1, 5:1:1, 5:0.5:1, etc.
[0029] Preferably, the coating power in step C is 7 kilowatts and the duty cycle is 1:20.
[0030] Preferably, the coating time in step C is 300-500 s, for example, 300 s, 350 s, 380 s, 400 s, 450 s or 500 s.
[0031] Preferably, the coating temperature in step C is 450-500°C, such as 450°C, 470°C, 490°C or 500°C.
[0032] In the present invention, after growing a layer of AlO film by ALD method, silane, ammonia and nitrous oxide are introduced into the tubular PECVD furnace tube in steps and batches, and a certain proportion is controlled, the coating time, coating power and duty cycle are adjusted to form a film layer structure with different refractive index and film thickness. The obtained back film structure not only has the effect of increasing the back short-circuit current and the back efficiency, but also has the effect of increasing the front opening voltage and FF and the front efficiency.
[0033] On the other hand, the present invention provides a bifacial PERC cell, wherein the bifacial PERC cell comprises a back film structure as described above for simultaneously improving the efficiency of the back and front sides of the bifacial PERC cell.
[0034] Compared with the prior art, the present invention has the following beneficial effects:
[0035] The back film structure of the present invention can simultaneously improve the back and front efficiencies of the bifacial PERC cell. The present invention improves the back conversion efficiency of the P-type bifacial PERC cell by improving the back film layer structure. The back film structure has a relatively good hydrogen passivation effect, and can also improve the opening voltage and FF of the cell, thereby achieving an improvement in the front conversion efficiency. The bifaciality of the P-type bifacial PERC cell can be increased by 1 to 2%, and the efficiency of the front of the cell can be increased by about 0.1%, thereby improving the benefits and competitiveness of the enterprise, and is very worthy of industrial application. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 Schematic diagram of the back film structure of the present invention, wherein the Si layer represents a P-type solar silicon wafer, 1 is an aluminum oxide (AlO) film, 2 is a silicon nitride (SiN) film, and 3 is a silicon oxynitride (SiON) film.
[0037] Figure 2 3 and 4 are reflectivity curves of the back film structures of Example 1 and Comparative Example 1 in the wavelength range of 300nm to 1200nm.
[0038] Figure 3 Schematic diagram of the structure of the back film structure of comparative example 2, wherein the Si layer represents a P-type solar silicon wafer, 1 is an aluminum oxide (AlO) film, 2 is a silicon nitride (SiN) film, 3 is a silicon oxynitride (SiON) film, and 4 is a silicon oxide (SiO) film. DETAILED DESCRIPTION
[0039] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0040] In the following embodiments of the present invention, the refractive index is tested by an ellipsometer, and the average reflectivity of the back film structure is tested by a D8 tester.
[0041] Example 1
[0042] In this embodiment, a back film structure is provided, which includes an aluminum oxide (AlO) film located on the back of the cell, a silicon nitride (SiN) film is provided on the aluminum oxide film, and a silicon oxynitride (SiON) film is provided on the silicon nitride film.
[0043] The preparation method comprises the following steps:
[0044] A. Place the battery cell with the back side facing upwards into the graphite plate, then place the graphite plate into the ALD plate chamber, and coat a layer of AlO film 1 on the back side of the battery for 10 times. The thickness of the AlO film 1 is 8-10 nm, and the refractive index is 1.56.
[0045] B. Place the battery cell obtained in step A with the back side facing up into a graphite boat, then place the graphite boat into a tubular PECVD, introduce ammonia and silane at a flow ratio of 6:1, and prepare SiN film 2 on AlO film 1. In this step, 6000 sccm of ammonia and 1000 sccm of silane are introduced, the coating time is 500 s, the coating power is 8 kW, the duty cycle is 1:15, the temperature is 450°C, the thickness of SiN film 2 is 60-65 nm, and the refractive index is 2.2.
[0046] C. Nitrous oxide, ammonia and silane were introduced at a flow ratio of 5:2:1 to prepare a SiON film 3 on the SiN film 2. 4000 sccm of nitrous oxide, 1600 sccm of ammonia and 800 sccm of silane were introduced. The coating time was 400 s, the coating power was 7 kW, the duty cycle was 1:20, the temperature was 450°C, the thickness of the SiON film 3 was 52-56 nm, and the refractive index was 1.8.
[0047] The back film structure of this embodiment has an average reflectivity of 8.0% in the wavelength range of 300nm to 1200nm. The wavelength corresponding to the lowest reflectivity in the back reflectivity curve is 900nm, and the total refractive index is 2.12.
[0048] Example 2
[0049] In this embodiment, a back film structure is provided, which includes an aluminum oxide (AlO) film located on the back of the cell, a silicon nitride (SiN) film is provided on the aluminum oxide film, and a silicon oxynitride (SiON) film is provided on the silicon nitride film.
[0050] The preparation method comprises the following steps:
[0051] A. Place the battery cell with the back side facing upwards into the graphite plate, then place the graphite plate into the ALD plate chamber, and coat a layer of AlO film 1 on the back side of the battery for 13 times. The thickness of the AlO film 1 is 10-12 nm, and the refractive index is 1.60.
[0052] B. Place the battery cell obtained in step A with the back side facing up into a graphite boat, then place the graphite boat into a tubular PECVD, introduce ammonia and silane at a flow ratio of 4.5:1, and prepare SiN film 2 on AlO film 1. In this step, 6300 sccm of ammonia and 1400 sccm of silane are introduced, the coating time is 600 s, the coating power is 8 kW, the duty cycle is 1:15, the temperature is 480°C, the thickness of SiN film 2 is 70-75 nm, and the refractive index is 2.3.
[0053] C. Nitrous oxide, ammonia and silane were introduced at a flow ratio of 6:2:1 to prepare a SiON film 3 on the SiN film 2. 4800 sccm of nitrous oxide, 1600 sccm of ammonia and 800 sccm of silane were introduced. The coating time was 320 s, the coating power was 7 kW, the duty cycle was 1:20, the temperature was 480°C, the thickness of the SiON film 3 was 40-45 nm, and the refractive index was 1.7.
[0054] The back film structure of this embodiment has an average reflectivity of 7.8% in the wavelength range of 300nm to 1200nm. The wavelength corresponding to the lowest reflectivity in the back reflectivity curve is 910nm, and the total refractive index is 2.16.
[0055] Example 3
[0056] In this embodiment, a back film structure is provided, which includes an aluminum oxide (AlO) film located on the back of the cell, a silicon nitride (SiN) film is provided on the aluminum oxide film, and a silicon oxynitride (SiON) film is provided on the silicon nitride film.
[0057] The preparation method comprises the following steps:
[0058] A. Place the battery cell with the back side facing upwards into a graphite plate, then place the graphite plate into an ALD plate-type chamber, and coat a layer of AlO film 1 on the back side of the battery for 15 times. The thickness of the AlO film 1 is 12-15 nm, and the refractive index is 1.63.
[0059] B. Place the battery cell obtained in step A with the back side facing up into a graphite boat, then place the graphite boat into a tubular PECVD, introduce ammonia and silane at a flow ratio of 4:1, and prepare SiN film 2 on AlO film 1. In this step, 6000 sccm of ammonia and 1500 sccm of silane are introduced, the coating time is 550 s, the coating power is 8 kW, the duty cycle is 1:15, the temperature is 500°C, the thickness of SiN film 2 is 80-85 nm, and the refractive index is 2.4.
[0060] C. Nitrous oxide, ammonia and silane were introduced at a flow ratio of 5:0.5:1 to prepare a SiON film 3 on the SiN film 2. 5000 sccm of nitrous oxide, 500 sccm of ammonia and 1000 sccm of silane were introduced. The coating time was 500 s, the coating power was 7 kW, the duty cycle was 1:20, the temperature was 500°C, the thickness of the SiON film 3 was 65-70 nmnm, and the refractive index was 2.0.
[0061] The back film structure of this embodiment has an average reflectivity of 8.7% in the wavelength range of 300nm to 1200nm. The wavelength corresponding to the lowest reflectivity in the back reflectivity curve is 960nm, and the total refractive index is 2.2.
[0062] Example 4
[0063] In this embodiment, a back film structure is provided, which includes an aluminum oxide (AlO) film located on the back of the cell, a silicon nitride (SiN) film is provided on the aluminum oxide film, and a silicon oxynitride (SiON) film is provided on the silicon nitride film.
[0064] The preparation method comprises the following steps:
[0065] A. Place the battery cell with the back side facing upwards into the graphite plate, then place the graphite plate into the ALD plate chamber, and coat a layer of AlO film 1 on the back side of the battery, coating 8 loops, with a thickness of 5-8 nm and a refractive index of 1.55;
[0066] B. Place the battery cell obtained in step A with the back side facing up into a graphite boat, then place the graphite boat into a tubular PECVD, introduce ammonia and silane at a flow ratio of 16:1, and prepare SiN film 2 on AlO film 1. In this step, 7800 sccm of ammonia and 650 sccm of silane are introduced, the coating time is 300 s, the coating power is 8 kW, the duty cycle is 1:15, the temperature is 450°C, the thickness of SiN film 2 is 38-42 nm, and the refractive index is 2.05.
[0067] C. Nitrous oxide, ammonia and silane were introduced at a flow ratio of 5:1:1 to prepare a SiON film 3 on the SiN film 2. 5000 sccm of nitrous oxide, 1000 sccm of ammonia and 1000 sccm of silane were introduced. The coating time was 300 s, the coating power was 7 kW, the duty cycle was 1:20, the temperature was 450°C, the thickness of the SiON film 3 was 38-42 nm, and the refractive index was 1.9.
[0068] The back film structure of this embodiment has an average reflectivity of 9.5% in the wavelength range of 300nm to 1200nm. The wavelength corresponding to the lowest reflectivity in the back reflectivity curve is 650nm, and the total refractive index is 2.0.
[0069] Example 5
[0070] In this embodiment, a back film structure is provided, which includes an aluminum oxide (AlO) film located on the back of the cell, a silicon nitride (SiN) film is provided on the aluminum oxide film, and a silicon oxynitride (SiON) film is provided on the silicon nitride film.
[0071] The preparation method comprises the following steps:
[0072] A. Place the battery cell with the back side facing upwards into the graphite plate, then place the graphite plate into the ALD plate chamber, and coat a layer of AlO film 1 on the back side of the battery for 10 times. The thickness of the AlO film 1 is 8-10 nm, and the refractive index is 1.56.
[0073] B. Place the battery cell obtained in step A with the back side facing up into a graphite boat, then place the graphite boat into a tubular PECVD, introduce ammonia and silane at a flow ratio of 4:1, and prepare SiN film 2 on AlO film 1. In this step, 6000 sccm of ammonia and 1500 sccm of silane are introduced, the coating time is 550 s, the coating power is 8 kW, the duty cycle is 1:15, and the temperature is 450°C. The thickness of SiN film 2 is 75-80 nm, and the refractive index is 2.4.
[0074] C. Nitrous oxide, ammonia and silane were introduced at a flow ratio of 5:2:1 to prepare a SiON film 3 on the SiN film 2. 4000 sccm of nitrous oxide, 1600 sccm of ammonia and 800 sccm of silane were introduced. The coating time was 400 s, the coating power was 7 kW, the duty cycle was 1:20 and the temperature was 450°C. The thickness of the SiON film 3 was 52-56 nm and the refractive index was 1.8.
[0075] The back film structure of this embodiment has an average reflectivity of 8.3% in the wavelength range of 300nm to 1200nm. The wavelength corresponding to the lowest reflectivity in the back reflectivity curve is 930nm, and the total refractive index is 2.19.
[0076] Comparative Example 1
[0077] In this comparative example, a back film structure is provided, which includes an aluminum oxide (AlO) film located on the back side of a cell, and a silicon nitride (SiN) film is disposed on the aluminum oxide film.
[0078] The preparation method comprises the following steps:
[0079] A. Place the cell with the back side facing upward on the graphite plate, then place the graphite plate in the ALD plate chamber, and coat a layer of AlO film 1 on the back side of the cell for 10 times. The thickness of the AlO film 1 is 8-10 nm, and the refractive index is 1.56.
[0080] B. Place the battery cell obtained in step A with the back side facing upward into a graphite boat, then place the graphite boat into a tubular PECVD, introduce ammonia and silane at a flow ratio of 6:1, and prepare SiN film 2 on AlO film 1. 6000 sccm of ammonia and 1000 sccm of silane are introduced. The coating time is 700 s, the coating power is 8 kW, the duty cycle is 1:15, the temperature is 450°C, the thickness of SiN film 1 is 84-88 nm, and the refractive index is 2.2.
[0081] Comparative Example 2
[0082] This comparative example provides a back film structure, which includes an aluminum oxide (AlO) film located on the back of the battery cell, a silicon nitride (SiN) film is provided on the aluminum oxide film, a silicon oxynitride (SiON) film is provided on the silicon nitride film, and a silicon oxide (SiO) film is provided on the silicon oxynitride (SiON) film.
[0083] The preparation method comprises the following steps:
[0084] A. Place the battery cell with the back side facing upwards into the graphite plate, then place the graphite plate into the ALD plate chamber, and coat a layer of AlO film 1 on the back side of the battery for 10 times. The thickness of the AlO film 1 is 8-10 nm, and the refractive index is 1.56.
[0085] B. Place the battery cell obtained in step A with the back side facing up into a graphite boat, then place the graphite boat into a tubular PECVD, introduce ammonia and silane at a flow ratio of 6:1, and prepare SiN film 2 on AlO film 1. In this step, 6000 sccm of ammonia and 1000 sccm of silane are introduced, the coating time is 500 s, the coating power is 8 kW, the duty cycle is 1:15, the temperature is 450°C, the thickness of SiN film 2 is 60-65 nm, and the refractive index is 2.2.
[0086] C. Nitrous oxide, ammonia and silane were introduced at a flow ratio of 5:2:1 to prepare a SiON film 3 on the SiN film 2. 4000 sccm of nitrous oxide, 1600 sccm of ammonia and 800 sccm of silane were introduced. The coating time was 400 s, the coating power was 7 kW, the duty cycle was 1:20 and the temperature was 450°C. The thickness of the SiON film 3 was 52-56 nm and the refractive index was 1.8.
[0087] D. Laughing gas and silane were introduced at a flow ratio of 14:1 to prepare a SiO film 4 on the SiON film 3. 8400 sccm of laughing gas and 600 sccm of silane were introduced. The coating power was 6.8 kW, the duty cycle was 1:25, the coating time was 100 s, the temperature was 450° C., the thickness of the SiO film 4 was 15-16 nm, and the refractive index was 1.5.
[0088] Comparative Example 3
[0089] The difference between this comparative example and Example 1 is that by adjusting the coating parameters in step A, that is, coating is performed 4 times so that the thickness of the aluminum oxide film is 3 nm and the refractive index is 1.5.
[0090] Comparative Example 4
[0091] The difference between this comparative example and Example 1 is that by adjusting the coating parameters in step A, that is, coating 22 times, the thickness of the aluminum oxide film is 20 nm and the refractive index is 1.7.
[0092] Comparative Example 5
[0093] The difference between this comparative example and Example 1 is that the thickness of the silicon nitride film is 15 nm and the refractive index is 1.95. In step B, the battery cell obtained in step A is placed in a graphite boat with the back side facing upward, and then the graphite boat is placed in a tubular PECVD, and ammonia and silane are introduced at a flow ratio of 17:1 to prepare a SiN film 2 on the AlO film 1. In this step, 8500 sccm of ammonia and 500 sccm of silane are introduced, the coating time is 110 s, the coating power is 8 kW, the duty cycle is 1:15, the temperature is 450°C, and the thickness of the SiN film 2 is 15 nm and the refractive index is 1.95.
[0094] Comparative Example 6
[0095] The difference between this comparative example and Example 1 is that the thickness of the silicon nitride film is 100 nm and the refractive index is 2.5. In step B, the battery cell obtained in step A is placed in a graphite boat with the back side facing upward, and then the graphite boat is placed in a tubular PECVD, and ammonia and silane are introduced at a flow ratio of 3:1 to prepare a SiN film 2 on the AlO film 1. In this step, 6000 sccm of ammonia and 2000 sccm of silane are introduced, the coating time is 700 s, the coating power is 8 kW, the duty cycle is 1:15, the temperature is 450°C, and the thickness of the SiN film 2 is 100 nm and the refractive index is 2.5.
[0096] Comparative Example 7
[0097] The difference between this comparative example and Example 1 is that the thickness of the silicon oxynitride film is 15 nm and the refractive index is 1.5. In step C, nitrous oxide, ammonia and silane are introduced at a flow ratio of 14:0.5:1 to prepare a SiON film 3 on a SiN film 2. 7000 sccm of nitrous oxide, 250 sccm of ammonia and 500 sccm of silane are introduced. The coating time is 110 s, the coating power is 7 kW, the duty cycle is 1:20, the temperature is 450-500° C., the thickness of the SiON film 3 is 15 nm and the refractive index is 1.5
[0098] Comparative Example 8
[0099] The difference between this comparative example and Example 1 is that the thickness of the silicon oxynitride film is 100nm and the refractive index is 2.2. In step C, laughing gas, ammonia and silane are introduced at a flow ratio of 1:4:1.5, and a SiON film 3 is prepared on a SiN film 2, 800sccm of laughing gas, 3200sccm of ammonia, 1200sccm of silane are introduced, the coating time is 700s, the coating power is 7 kilowatts, the duty cycle is 1:20, the temperature is 450-500°C, and the thickness of the SiON film 3 is 100nm and the refractive index is 2.2.
[0100] like Figure 2 The reflectivity curves of the back film structures of Example 1 and Comparative Example 1 in the wavelength range of 300nm to 1200nm are given. From the test results of the figure, it is obtained that the average reflectivity of the back film structure of Example 1 is 8.0%, and the corresponding wavelength of the lowest reflectivity in the curve is 900nm. The average reflectivity of Comparative Example 1 is 10.0%, and the corresponding wavelength of the lowest reflectivity in the curve is 780nm.
[0101] The batteries prepared by the preparation methods of Examples 1 to 5 and Comparative Examples 1 to 8 were subjected to IV tests on the front and back batteries to characterize the electrical properties of the back and front batteries. The electrical properties data of the back batteries are shown in Table 1 below:
[0102] Table 1 Back electrical properties
[0103]
[0104] The front electrical performance data is shown in Table 2 below:
[0105] Table 2 Front electrical properties
[0106]
[0107] It can be seen from Table 1 that the back short-circuit current Isc in Example 1 is significantly improved, with a gain of about 136mA. This is mainly because the reflectivity of the film made by the back film structure and its coating method in Example 1 is about 2% lower than that of the control example. Therefore, the Isc gain is more obvious, and the back parallel resistance is increased, the filling factor FF is improved, and the conversion efficiency EFF is significantly improved.
[0108] It can be seen from Table 2 that the front opening voltage in Example 1 is increased by 0.6 mV, and the fill factor FF is increased by 0.19%. Due to the unique back film structure and back reflectivity curve, it is beneficial to the overall passivation of the battery, so the opening voltage and FF gain are more obvious.
[0109] The applicant declares that the present invention uses the above-mentioned embodiments to illustrate the back film structure of the present invention and its preparation method and application, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A back film structure for simultaneously improving the efficiency of the back and front sides of a bifacial PERC, characterized in that: The back film structure is composed of an aluminum oxide film, a silicon nitride film and a silicon oxynitride film located on the back of the cell, wherein a silicon nitride film is disposed on the aluminum oxide film, and a silicon oxynitride film is disposed on the silicon nitride film; The aluminum oxide film has a thickness of 5 to 15 nm and a refractive index of 1.55 to 1.63; The silicon nitride film has a thickness of 60 to 80 nm and a refractive index of 2.2 to 2.4; The silicon oxynitride film has a thickness of 20 to 90 nm and a refractive index of 1.8; The lowest point of the reflectivity curve of the back film structure in the wavelength range of 300nm to 1200nm is located at 650 to 1000nm; The back film structure has an average reflectivity of 7.5% to 11% in the wavelength range of 300nm to 1200nm; The back film structure is prepared by the following method, which comprises the following steps: A. Place the cell with the back side facing up into the graphite plate, then place the graphite plate into the ALD plate chamber to coat a layer of aluminum oxide film on the back side of the cell; B. Place the battery cell obtained in step A with the back side facing upward into a graphite boat, then place the graphite boat into a tubular PECVD, introduce ammonia and silane gases, and coat the aluminum oxide film to prepare a silicon nitride film; C. introducing laughing gas, ammonia gas and silane gas to coat the silicon nitride film to prepare a silicon oxynitride film, thereby obtaining the back film structure.
2. The back film structure according to claim 1, characterized in that: The aluminum oxide film has a thickness of 8 to 10 nm and a refractive index of 1.
56.
3. The back film structure according to claim 1, characterized in that: The thickness of the silicon oxynitride film is 40-60 nm.
4. The back film structure according to claim 1, characterized in that: The total thickness of the aluminum oxide film, the silicon nitride film and the silicon oxynitride film is 80 to 160 nm, and the total refractive index is 2.0 to 2.
35.
5. The back film structure according to claim 1, characterized in that: The lowest point of the reflectivity curve of the back film structure in the wavelength range of 300nm to 1200nm is located at 850 to 950nm.
6. The method for preparing a back film structure according to any one of claims 1 to 5, wherein the method comprises the following steps: A. Place the cell with the back side facing up into the graphite plate, then place the graphite plate into the ALD plate chamber to coat a layer of aluminum oxide film on the back side of the cell; B. Place the battery cell obtained in step A with the back side facing upward into a graphite boat, then place the graphite boat into a tubular PECVD, introduce ammonia and silane gases, and coat the aluminum oxide film to prepare a silicon nitride film; C. introducing laughing gas, ammonia gas and silane gas to coat the silicon nitride film to prepare a silicon oxynitride film, thereby obtaining the back film structure.
7. The preparation method according to claim 6, characterized in that: The silane in step B is SiH4.
8. The preparation method according to claim 6, characterized in that: The flow ratio of ammonia and silane introduced in step B is 8:1 to 3:
1.
9. The preparation method according to claim 6, characterized in that: The coating power in step B is 8 kilowatts and the duty cycle is 1:
15.
10. The preparation method according to claim 6, characterized in that: The coating time in step B is 300-600s.
11. The preparation method according to claim 6, characterized in that: The coating temperature in step B is 450-500°C.
12. The preparation method according to claim 6, characterized in that: The flow ratio of the laughing gas, ammonia and silane introduced in step C is 14:2:1 to 5:0.5:
1.
13. The preparation method according to claim 6, characterized in that: The coating power in step C is 7 kilowatts and the duty cycle is 1:
20.
14. The preparation method according to claim 6, characterized in that: The coating time in step C is 300-500s.
15. The preparation method according to claim 6, characterized in that: The coating temperature in step C is 450-500°C.
16. A bifacial PERC cell, characterized in that: The bifacial PERC cell comprises a back film structure for improving the efficiency of both the back and front sides of the bifacial PERC cell as described in any one of claims 1 to 5.
Citation Information
Patent Citations
Back film for improving double-sided rate of P-type double-sided battery and preparation method thereof
CN110957378A
Back surface film structure for improving back surface efficiency of double-sided PERC battery and film coating method thereof
CN111106184A
Back film structure and double-sided PERC battery
CN214705940U